Low-Power CMOS Integrated Hall Switch Sensor - Rongshan Wei; Shizhong Guo; Shanzhi Yang (Active and Passive Electronic Components)
This paper presents an integrated Hall switch sensor based on SMIC 0.18 µm CMOS technology. The system includes a front-end Hall element and a back-end signal processing circuit. By optimizing the structure of the Hall element and using the orthogonal coupling and spinning current technology, the offset voltage can be suppressed effectively. The simulation results showed that the Hall switch can eliminate offset voltage greater than 1 mV at 3.3 V supply voltage. Two modes of the Hall switch circuit, the awake mode and the sleep mode, were realized by using clock logic signals without compromising the performance of the Hall switch, thereby reducing power consumption. The test results showed that the operate point and the release point of the switch were within the range of 3–7 mT at 3.3 V supply voltage. Meanwhile, the current consumption is 7.89 µA.